Education on Breakfast and Iron Supplement Intake to Control the Incidence of Anemia Among Adolescent Girls at SMKN 1 Langsa City - Marta Aditya Pratiwi; Romi Jayadi; Raisha Octavariny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Anemia among adolescent girls remains a health issue that impacts growth, academic performance, and productivity. Skipping breakfast and low adherence to taking iron-folic acid supplements (TTD) are factors that increase the risk of anemia. This community service activity aimed to increase the knowledge and awareness of adolescent girls at SMKN 1 Langsa City regarding the importance of breakfast and TTD consumption as measures to prevent anemia. The methods employed included coordination with the school, administering a pre-test, conducting health education sessions using presentations and leaflets, facilitating interactive discussions, screening hemoglobin levels, distributing leaflets, and administering a post-test for evaluation. Sixty-eight female students participated in the activity. The results showed that 34 participants (50.0%) had a habit of eating breakfast, 29 participants (42.6%) consumed TTD, and 18 participants (26.5%) were found to have anemia based on hemoglobin screening. Knowledge evaluation revealed an increase in the average score from 61.5 in the pre-test to 86.8 in the post-test, representing a rise of 25.3 points. Furthermore, the participants demonstrated enthusiasm and active participation throughout the event. This community service activity was effective in enhancing the knowledge and awareness of adolescent girls regarding the importance of breakfast, TTD consumption, and anemia prevention. It is recommended that health education combined with hemoglobin screening be implemented on an ongoing basis through collaboration among schools, healthcare professionals, and parents to support anemia prevention among adolescent girls.